Educational foundations in addressing intellectual deviations from the Sunnah "Inductive stud " (Journal of the College of Basic Education, 2022)
The research dealt with one of the issues through the past and contemporary stages of history, and renewed in Islamic societies and elsewhere, intellectual deviation and ways to prevent it educationally, in light of the hadiths of the Prophet through words, deeds and reports. They are valid for every time and place. He settled in them, making them backward societies in all aspects of their lives, The research was divided into three topics, which mentioned in the first the concept of deviation and the linguistic and idiomatic thought, and the second the reasons that lead to this deviation from the lack of understanding of the legal texts that they are correct. The educational foundations that the Prophet’s Sunnah came about through types of treatments of moving away from manifestations of exaggeration and warning against falling into temptation, avoiding difference in religion, incorrect dealing with the texts of Sharia, following the advocates of misguidance and using the method of dialogue for education and education, and then society is immunized from those destructive ideas.